Rising public expenditure and economic growth, was Wagner right? Evidence from Nigeria - Richardson Kojo Eedme; Chukwuemeka Valentine Okolo; Chinazor Jane-Francis Idenyi; Chiamaka Faith Okolomike (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study empirically tests if the Wagner’s law stands for the Nigerian economy using data for the period 1981-2015. Form the results, economic, social and community services expenditure show highly significant values suggesting that these sectors are very much needed and still adds value to the economy. The results of the Granger causality analysis indicates that there is a bi-directional causality between economic growth and government spending, which posit to a high level of accuracy that Wagner’s law holds for Nigeria. The result suggests that economic growth has an important role to play in determining government spending because as the economy grows, it expands and for this, government need to expand its spending to meet up with the demands of the expansion. There is therefore the need for curtail the rapid growth of its size above the optimum level that stimulates rise in expenditure. Any further expansion in expenditure should focus on economic, social and community services since they are growth enhancing.